Differential abundance analysis of mesocarp protein from high- and low-yielding oil palms associates non-oil biosynthetic enzymes to lipid biosynthesis. Issue 1 (December 2015) - Ooi, Tony; Yeap, Wan; Daim, Leona; Ng, Boon; Lee, Fong; Othman, Ainul; Appleton, David; Chew, Fook; Kulaveerasingam, Harikrishna
Abstract Background The oil palmElaeis guineensis Jacq. which produces the highest yield per unit land area of the oil crops is the most important commercial oil crop in South East Asia. The fleshy mesocarp of oil palm fruit, where oil is mostly derived from, contains up to 90 % dry weight of oil (one of the most concentrated in plant tissues). Hence, there is attention given to gain insights into the processes of oil deposition in this oil rich tissue. For that purpose, two-dimensional differential gel electrophoresis (DIGE) coupled with western assays, were used here to analyze differential protein levels in genetically-related high-and low-yielding oil palm mesocarps. Results From the DIGE comparative analysis in combination with western analysis, 41 unique differentially accumulated proteins were discovered. Functional categorization of these proteins placed them in the metabolisms of lipid, carbohydrate, amino acids, energy, structural proteins, as well as in other functions. In particular, higher abundance of fructose-1, 6-biphosphate aldolase combined with reduced level of triosephosphate isomerase and glyceraldehyde-3-phosphate dehydrogenase may be indicative of important flux balance changes in glycolysis, while amino acid metabolism also appeared to be closely linked with oil yield. Conclusions Forty-one proteins in several important biological pathways were identified as exhibiting differential in abundance at critical oil production stages. These confirm that oil yield is a complex trait involving the regulation of genes in multiple biological pathways. The results also provide insights into key control points of lipid biosynthesis in oil palm and can assist in the development of genetic markers for use in oil palm breeding programmes.